Accuracy of ultrasound in the detection of renal scarring in paediatric patients presenting with urinary tract infection. (September 2015) - Aggarwal, Reena; Holmes, Rachael; Rickett, A.
Abstract : Purpose: Urinary tract infection (UTI) is common in childhood with renal scarring documented in up to 15% after a first UTI. This has significant long-term complications including hypertension and renal failure and therefore it is important that we detect these changes early to prevent this. It is widely accepted that dimercaptosuccinic acid (DMSA) scintigraphy is the most sensitive method to detect renal scarring, however there is variable evidence for the role of ultrasound. The aim of this study is to assess the accuracy of ultrasound to detect renal scarring using DMSA scan as gold standard. Methods and materials: A retrospective radiology information system (RIS) search was performed to identify paediatric patients presenting with UTI who underwent DMSA scan over a seven-month period. Imaging findings were compared to that of the preceding ultrasound. Results: The study reviewed 128 patients. Ultrasound correlated with DMSA in 99 patients. Forty-three patients (34%) had renal scarring on DMSA, however, only 16 of these (37%) were detected on preceding ultrasound. Of the 110 patients with normal ultrasound, the DMSA scan showed renal scarring in 27 (25%). The sensitivity, specificity, positive and negative predictive values are 37%, 98%, 89% and 75% respectively. Conclusion: This study suggests only a small percentage of renal scars are detected by ultrasound and therefore this should be used in conjunction with DMSA scintigraphy when imaging for this purpose.